Degradation of the polysaccharide component of gonococcal lipopolysaccharide by gonococcal and meningococcal sonic extracts. - Apicella, M A (1978)
An extract made from the supernatant of Neisseria gonorrhoeae Gc2 strain 1291 degraded the Gc2 polysaccharide antigen. Chemical analysis of this polysaccharide indicated it contains glucose, galactose, glucosamine, galactosamine, glucosamine-6-phosphate, heptose, 2-keto-3-deoxyotonate, and ethanolamine and is the polysaccharide component of gonococcal lipopolysaccharide. Degradation of the polysaccharide by sonic extracts resulted either in complete loss of antigenicity and immunogenicity or in partial degradation to subunits that could inhibit the Gc2-specific hemagglutination inhibition. The factors responsible for degradation were destroyed by heating at 100 degrees C for 5 min or by Pronase digestion, but were unaffected by ribonuclease, deoxyribonuclease, Mg2+, Ca2+, or ethylenediaminetetraacetic acid. The process was pH dependent, with optimal activity occurring at pH 7. Sonic extract supernatants from group B and C meningococcal strains contained degrading properties, whereas similar extracts produced from Escherichia coli, Staphylococcus aureus, Klebsiella pneumoniae, and Streptococcus pneumoniae type II failed to degrade the Gc2 polysaccharide.